Surface charge density prediction method of friction nanometer generator based on modified chitosan material
By modifying chitosan with polyphenol and constructing a surface charge density prediction model, the problem of difficult biomaterials to achieve high-performance negative polarity triboelectric nanogenerators is solved, the electrical output performance is improved and the research gap is filled.
Patent Information
- Application Number
- CN202411682078.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-22
AI Technical Summary
It is difficult for existing biomaterials to establish high-performance negative polarity biotrigel nanogenerators, and chitosan has insufficient research on the friction polarity modification mechanism and prediction model.
Chitosan is chemically modified by polyphenols, modified chitosan is prepared, and a surface charge density prediction model of friction nanogenerators based on modified chitosan materials is constructed.
The transformation of chitosan friction electrode polarity has been achieved, the electrical output performance of friction nanogenerators has been improved, and the theoretical basis for the development of high-performance biological TENGs has been provided.
Smart Images

Figure CN119619639A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of nano energy, and in particular to a method for predicting the surface charge density of a friction nanogenerator based on modified chitosan material. Background Art
[0002] As a promising solution for converting mechanical energy into electrical energy, triboelectric nanogenerators (TENGs) provide a self-sustaining power source for the development of electronic technology. The selection of materials is crucial to improving the performance of TENGs. Materials are arranged in a triboelectric series according to their tendency to gain or lose electrons, and this behavior is significantly affected by the electron affinity of surface functional groups. In the field of implantable medical devices, it is difficult to establish an effective and high-performance bio-TENG for TENGs designed entirely with biomaterials due to the lack of negative triboelectric polarity materials. Therefore, it is necessary to modify and design existing biomaterials and develop high-performance negative polarity biomaterials. At the same time, models are established to optimize and predict the triboelectric properties of materials.
[0003] Chitosan is a biopolymer extracted from chitin. It has become a promising triboelectric material due to its biocompatibility, degradability and natural abundance. In previous triboelectric studies, chitosan was only used as a positive triboelectric material. Although there have been many efforts to improve its triboelectric output performance, including progress in physical doping and ion embedding, the mechanism of chitosan triboelectric polarity modification and related prediction models have not been fully studied. Designing surface functional groups and molecular structures can increase the charge density and even change the triboelectric polarity. Chitosan contains a large number of amino and hydroxyl groups, which make important contributions to the electron donating ability and are also potential sites for chemical modification, indicating that surface chemical modification has the potential to change the triboelectric charge behavior and increase the degree of modification. Therefore, if the surface charge density of the triboelectric nanogenerator using modified chitosan materials can be predicted, it will be of great significance to guide the optimization of the triboelectric polarity of the modified chitosan and improve the electrical output performance of the triboelectric nanogenerator. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to propose a method for predicting the surface charge density of a friction nanogenerator based on modified chitosan materials. Chitosan is modified by polyphenols to achieve the triboelectric polarity transformation of chitosan. Microscopic characterization methods are used to quantify key parameters and construct a surface charge density prediction model for a friction nanogenerator based on modified chitosan materials. The research covers chitosan modification, triboelectric polarity testing and quantitative characterization, and prediction model construction. It includes modifying different forms of chitosan with specific polyphenols, constructing triboelectric nanogenerator tests with commonly used triboelectric materials, and using a variety of techniques to obtain data to build models and verify optimization. This research can fill the gaps related to chitosan, help develop high-performance bio-TENG, promote its application in the biomedical field, and open up a path for the research and development of new bio-triboelectric materials, which is of great significance to the development of TENG and biomaterials science.
[0005] In order to solve the above problems, the present invention provides a method for predicting the surface charge density of a tribo-nanogenerator based on a modified chitosan material, which comprises the following steps:
[0006] S1. Preparation of modified chitosan:
[0007] Polyphenol is used as a modification material to chemically modify chitosan to obtain modified chitosan;
[0008] S2. Triboelectric polarity test and quantitative characterization of modified chitosan:
[0009] The modified chitosan is brought into contact with different materials in a known triboelectric series to generate an electric signal, and the relative positive and negative values of the electric signal and the saturated charge density are obtained, and the position of the modified chitosan in the known triboelectric series is determined according to the relative positive and negative values of the electric signal;
[0010] S3. Obtain the surface potential energy and saturated charge density of the modified chitosan and the paired material:
[0011] A friction nanogenerator is composed of modified chitosan and a pairing material, and the surface potential energy of the pairing material, the surface potential energy of the modified chitosan, and the saturated charge density of the friction nanogenerator are obtained respectively.
[0012] S4. Construction of a surface charge density prediction model for triboelectric nanogenerators based on modified chitosan materials:
[0013] The surface charge density prediction model of the triboelectric nanogenerator based on modified chitosan material is:
[0014] σ c =a(V1-V2) 2 -b(V1-V2)-c
[0015] C p =f(V2)
[0016] Where: c is the surface charge density of the triboelectric nanogenerator; V1 is the surface potential energy of the paired material; V2 is the surface potential energy of the modified chitosan; a, b and c are the fitting parameters corresponding to different paired materials; C p is the polyphenol concentration; f is the functional relationship between the polyphenol concentration and the surface potential energy of the modified chitosan;
[0017] According to the surface charge density prediction model of the friction nanogenerator based on modified chitosan material, when the pairing materials are determined, the surface charge density of the friction nanogenerator can be directly determined according to the polyphenol concentration; thereby guiding the optimization of the friction electric polarity of the modified chitosan and improving the electrical output performance of the friction nanogenerator.
[0018] Preferably, step S1 specifically includes:
[0019] S11, preparing a polyphenol solution: dissolving the polyphenol in a solvent to form a polyphenol concentration of C p The solution of C p The value range is (0%, 50%]; the solvent is a mixture of one or more of deionized water, ethanol, acetone and tetrachloromethane;
[0020] S12, preparing a chitosan solution: dissolving chitosan in an acid solvent, and cleaning it to remove impurities and pollutants to obtain a chitosan solution; the acid solvent is a mixture of one or more of acetic acid, hydrochloric acid, nitric acid and phosphoric acid;
[0021] S13, mixing the chitosan solution of S12 with the polyphenol solution of S11, and then placing in a mold to dry, to obtain modified chitosan.
[0022] Preferably, the materials in the known triboelectric sequence in step S2 include but are not limited to polyamide, thermoplastic polyurethane, polypropylene, polyethylene terephthalate, polydimethylsiloxane, polytetrafluoroethylene and polyperfluoroethylene propylene.
[0023] Preferably, step S3 specifically includes the following sub-steps:
[0024] S31, forming a friction nanogenerator by using modified chitosan and a matching material, wherein the friction nanogenerator is in a contact-separation mode;
[0025] S32, using an electrometer to measure the charge signal of the contact and separation process, and obtaining the saturation charge density of the friction nanogenerator through the signal amplitude;
[0026] S33. The surface potential energy of the modified chitosan material and the surface potential energy of the paired material during the contact separation process were measured using a scanning Kelvin probe microscope.
[0027] Preferably, step S4 specifically includes the following sub-steps:
[0028] S41. Based on the surface potential energy, a surface charge density prediction model of the friction nanogenerator in step S3 is constructed, and its expression σ c for:
[0029] σ c =a(V1-V2) 2 -b(V1-V2)-c (1)
[0030] Where: cis the surface charge density of the triboelectric nanogenerator; V1 is the surface potential energy of the paired material; V2 is the surface potential energy of the modified chitosan; a, b and c are the fitting parameters corresponding to different paired materials;
[0031] S42, due to the surface charge density σ c It cannot be directly measured and obtained, and the saturation charge density σ must be measured first I , and then calculated by expression, the expression is:
[0032]
[0033] Where: z is the separation distance between the paired material and the modified chitosan; d1 and d2 are the thickness of the paired material and the modified chitosan, respectively; ε0 is the dielectric constant of air; ε1 and ε2 are the dielectric constants of the paired material and the modified chitosan, respectively;
[0034] S43. The surface potential energy of modified chitosan is related to the modification degree, which corresponds to the polyphenol concentration. Therefore, the surface potential energy model of modified chitosan material is established according to the polyphenol concentration:
[0035] V2=f(C p ), (3)
[0036] Where: C p is the polyphenol concentration;
[0037] S44. According to formulas (1) and (3), a surface charge density prediction model of the friction nanogenerator based on modified chitosan is obtained. When different pairing materials are used to form a friction nanogenerator with the modified chitosan material, a surface charge density prediction model of the friction nanogenerator based on the modified chitosan material with different fitting parameters is obtained. The surface charge density prediction model of the friction nanogenerator based on modified chitosan using different pairing materials can directly obtain the surface charge density of the friction nanogenerator according to the polyphenol concentration, thereby guiding the optimization of the friction electric polarity of the modified chitosan and improving the electrical output performance of the friction nanogenerator.
[0038] Preferably, the chitosan in step S1 includes but is not limited to non-deacetylated chitin, chitosan with different deacetylation degrees, quaternary ammonium salt chitosan and carboxymethyl chitosan.
[0039] Preferably, the polyphenols in step S1 include but are not limited to tannic acid, catechins, dopamine and anthocyanins.
[0040] Preferably, the form of the modified chitosan in step S1 includes but is not limited to film, hydrogel, aerogel and block.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The present invention can directly obtain the surface charge density of the friction nanogenerator based on the modified chitosan material according to the modification degree of the modified chitosan material, effectively filling the current research gap in the modification mechanism and prediction model of chitosan friction electrode polarity, and providing a solid theoretical basis for the subsequent in-depth study of the application of chitosan in the field of triboelectricity.
[0043] 2. The successful development of high-performance bio-TENG has strongly promoted the widespread application of triboelectric nanogenerators in fields such as implantable devices, providing new ideas and technical means to solve the energy supply problem of equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The schematic diagram of the chemical interaction mechanism of chitosan modified by tannic acid in the present invention;
[0045] Figure 2 1 is a comparison diagram of Fourier transform infrared spectra of chitosan before and after modification in an embodiment of the present invention;
[0046] Figure 3 is a comparison diagram of X-ray photoelectron spectra of chitosan before and after modification in an embodiment of the present invention;
[0047] Figure 4 Surface roughness comparison of chitosan before and after modification in the embodiment of the present invention;
[0048] Figure 5 The X-ray diffraction comparison diagram of chitosan before and after modification in the embodiment of the present invention;
[0049] Figure 6 The figure is a comparison of the mechanical properties of chitosan before and after modification in the embodiment of the present invention;
[0050] Figure 7 Schematic diagram of the structure of a triboelectric nanogenerator based on modified chitosan in an embodiment of the present invention;
[0051] Figure 8 The saturated charge density and triboelectric polarity generated by chitosan and different paired materials before and after modification in the embodiments of the present invention;
[0052] Fig. 9 is the surface potential energy of the paired materials, chitosan before and after modification in the embodiments of the present invention;
[0053] Fig.10 This is the parameter fitting of the surface charge prediction model of tannic acid modified chitosan in the embodiment of the present invention.
[0054] Fig.11 : The positions of modified chitosan with different modification degrees in the triboelectric series in the embodiments of the present invention.
[0055] Fig.12 The flow chart for predicting the surface charge density of the triboelectric nanogenerator based on the modified chitosan material of the present invention is DETAILED DESCRIPTION
[0056] A method for predicting the surface charge density of a triboelectric nanogenerator based on modified chitosan materials, such as Fig.12 As shown, the following steps are included:
[0057] S1. Preparation of modified chitosan:
[0058] Polyphenol is used as a modification material to chemically modify chitosan to obtain modified chitosan; the specific steps are:
[0059] S11, preparing a polyphenol solution: dissolving the polyphenol in a solvent to form a polyphenol concentration of C p The polyphenol solution, the C p The value range is (0%, 50%].
[0060] Polyphenol concentration refers to the weight ratio of polyphenol to chitosan. The polyphenol solution prepared according to the polyphenol concentration is called polyphenol concentration C. p The solvent is a mixture of one or more of deionized water, ethanol, acetone and tetrachloromethane. Polyphenols include but are not limited to tannic acid, catechins, dopamine and anthocyanins.
[0061] S12, preparing a chitosan solution: dissolving chitosan in an acid solvent, and cleaning it to remove impurities and pollutants to obtain a chitosan solution;
[0062] The acid solvent is a mixture of one or more of acetic acid, hydrochloric acid, nitric acid and phosphoric acid.
[0063] Chitosan includes, but is not limited to, non-deacetylated chitin, chitosan with different degrees of deacetylation, quaternary ammonium salt chitosan or carboxymethyl chitosan.
[0064] S13, mixing the pretreated chitosan solution with the polyphenol solution, and then placing the mixture in a mold for drying to obtain a modified chitosan material.
[0065] The forms of modified chitosan include, but are not limited to, films, hydrogels, aerogels, and monoliths.
[0066] Using polyphenol solutions with different polyphenol concentrations will result in modified chitosan with different properties. This is because the reaction between polyphenol and chitosan changes the properties of chitosan. Using different polyphenol concentrations will result in different amino content consumed, so using different polyphenol concentrations will result in different degrees of modification. The degree of modification is defined as the amino content consumed by the modification using elemental analysis technology. X-ray photoelectron spectroscopy technology can be used to characterize the changes in chemical bonds formed by the reaction of polyphenol and chitosan, thereby obtaining the degree of modification corresponding to different polyphenol concentrations.
[0067] S2. Triboelectric polarity test and quantitative characterization of modified chitosan
[0068] The modified chitosan obtained from S1 is brought into contact with different materials in a known triboelectric series to generate an electrical signal, and the electrical signal during the contact-separation process is measured to obtain the saturated charge density. The triboelectric polarity of the chitosan is determined based on the relative positive and negative values of the electrical signal; thus, the position of the modified chitosan of S1 in the triboelectric series is obtained.
[0069] The saturation charge density can be measured using an electrometer. The specific method is as follows: the electrometer measures the charge signal of the contact and separation process, and obtains the saturation charge density through the signal amplitude, and obtains the triboelectric polarity by displaying the relative positive and negative waveform.
[0070] The triboelectric sequence refers to the regular sequence of the magnitude and positive and negative charges of two different substances when they are rubbed together. Known materials in the triboelectric sequence include but are not limited to polyamide, thermoplastic polyurethane, polypropylene, polyethylene terephthalate, polydimethylsiloxane, polytetrafluoroethylene and polyperfluoroethylene propylene. Modified chitosan materials with different degrees of modification will have different positions in the triboelectric sequence, such as Fig.11 shown.
[0071] S3. Obtain the surface potential energy and saturated charge density of the modified chitosan and the paired material:
[0072] S31. According to the measured triboelectric polarity of the modified chitosan, a pairing material is selected, and a triboelectric nanogenerator is formed by the modified chitosan and the pairing material, such as Figure 7 As shown, the friction nanogenerator is in contact-separation mode; the paired material is a material in a known friction electric series;
[0073] S32. Measure the saturated charge density of the modified chitosan and the paired material during the contact separation process. The same method as in S2 can be used, that is, use an electrometer to measure the charge signal of the contact separation process, and obtain the saturated charge density through the signal amplitude; if the saturated charge density of the friction nanogenerator has been measured in step S2, it can be used here directly without measuring again.
[0074] S33, using surface potential analysis technology to quantify the potential energy of the material; in this embodiment, the surface potential energy of the modified chitosan and the surface potential energy of the paired material during the contact separation process are measured using a scanning Kelvin probe microscope. If the surface potential energy of the paired material or the modified chitosan is known, it can be used directly here without measuring again.
[0075] S4. Construction of a surface charge density prediction model for triboelectric nanogenerators based on modified chitosan materials:
[0076] S41. According to the surface potential energy, a surface charge density prediction model of the friction nanogenerator in step S3 is constructed, and its expression σ c for:
[0077] σ c =a(V1-V2) 2 -b(V1-V2)-c (1)
[0078] Where: c is the surface charge density of the friction nanogenerator; V1 is the surface potential energy of the paired material; V2 is the surface potential energy of the modified chitosan; a, b and c are the fitting parameters corresponding to different paired materials; the surface charge density of the friction nanogenerator in this embodiment represents the surface charge density generated between the two materials used in the friction nanogenerator.
[0079] S42, due to the surface charge density σ c It cannot be directly measured and obtained, and the saturation charge density σ must be measured first I , and then calculated by expression, the expression is:
[0080]
[0081] Where: z is the separation distance between the paired material and the modified chitosan; d1 and d2 are the thickness of the paired material and the modified chitosan, respectively; ε0 is the dielectric constant of air; ε1 and ε2 are the dielectric constants of the paired material and the modified chitosan, respectively;
[0082] S43. It can be seen that the surface charge density of the triboelectric nanogenerator is determined by the surface potential energy of the modified chitosan and the surface potential energy of the paired material. In the triboelectric nanogenerator, the surface potential energy of each material has a fixed value, that is, the surface potential energy of the paired material can be directly determined according to the paired material energy. The surface potential energy of the modified chitosan is related to the degree of modification, and the degree of modification corresponds to the polyphenol concentration one by one. Therefore, the surface potential energy model of the modified chitosan can be established according to the polyphenol concentration:
[0083] V2=f(C p ), (3)
[0084] Where: Cp is the polyphenol concentration;
[0085] The surface potential energy model of modified chitosan can be determined by the point plotting method or fitting method.
[0086] S44, formula (1) and (3) are combined to obtain the modification concentration and surface charge density prediction model of the modified chitosan-based triboelectric nanogenerator.
[0087] When different pairing materials are used with modified chitosan materials to form a friction nanogenerator, a surface charge density prediction model of the friction nanogenerator based on modified chitosan materials with different fitting parameters is obtained. In actual use, the surface charge density prediction model of the friction nanogenerator based on modified chitosan using different pairing materials can directly obtain the surface charge density of the friction nanogenerator based on modified chitosan materials with different modification degrees, and no longer requires complex testing, thereby guiding the optimization of the friction electric polarity of modified chitosan and improving the electrical output performance of the friction nanogenerator.
[0088] In a specific embodiment of the present invention, chitosan is modified by using tannic acid solutions of different concentrations to obtain modified chitosan films.
[0089] In the process of example verification, different contents of tannic acid, specifically tannic acid / chitosan weight ratio of 0%, 5%, 10%, 15%, 20%, where 0%, 5%, 10%, 15%, 20% are different polyphenol concentrations, are added to the chitosan matrix through a simple neutralization process at room temperature to obtain uniformly mixed chitosan / tannic acid composite films (CS, CT5, CT10, CT15, CT20), where the front CT is the modified chitosan, and the number behind is the polyphenol concentration after removing the percentage sign. Figure 1 As shown in Figure 2, the cross-linked network of the composite membrane is formed by hydrogen bonds and covalent bonds. Tannic acid and chitosan interact with each other through Schiff base reaction to form imine bonds. Figure 2 The CS, CT10 and CT20 films were further characterized by ATR-FTIR spectroscopy at 3250 cm -1 (NH and OH stretching), 1648cm -1 (-NHCO- bond) and 1540cm -1 A characteristic absorption band was found at (NH bending), which is consistent with the inherent chemical structure of chitosan. In addition, the CT20 film has a peak absorption band at 1718 cm -1 There is a weak peak at 3500-3000 cm, which is the characteristic of the carbonyl (C=O) group from tannic acid. In the CT10 and CT20 films, the hydrogen bonding interaction between tannic acid and the -OH and -NH2 groups in chitosan is at 3500-3000 cm -1There is a clear expansion zone in between.
[0090] The surface amino composition of chitosan membranes was revealed by X-ray photoelectron spectroscopy (XPS) N1s spectrum (see Figure 3 ). Table 1 summarizes the relative content of consumed amino groups. The change in -NH2 content between CT and CS membranes can be used as an indicator of the extent of Schiff base reaction. Figure 4 The surface morphology of the membranes was observed by atomic force microscopy (AFM), and the calculated root mean square roughness was 3.43, 9.21, and 11.86 nm, respectively. The introduction of tannic acid enhanced the surface roughness at the nanoscale through intermolecular cross-linking, resulting in increased exposure of functional groups on the membrane surface. The crystal structure of the chitosan film was characterized by X-ray diffraction (XRD), as shown in Figure 2. Figure 5 As shown. The XRD spectrum of the CS film shows that the diffraction peaks are located at 2θ=8.5°, 11.6° (two hydrated crystal peaks) and 22.4° (amorphous diffraction peak). After the addition of tannic acid, the peak intensities at 8.5°, 11.6° and 20.0° decreased, indicating that the cross-linking between chitosan and tannic acid molecules reduced the crystallinity of the CT film. In addition, the increase in tannic acid content caused the amorphous diffraction peak of tannic acid at 25.0° in the CT film to shift slightly upward. The addition of tannic acid affects the interaction between molecules and may also affect the structural arrangement within the membrane, thereby changing the physical properties of the membrane. Figure 6 Tensile strain-stress curves of CS and CT films to characterize the mechanical properties of the materials. The CS film has a tensile strength of 25.2 MPa and an elongation at break of 46.2%. In comparison, the tensile strength of the CT10 film is significantly improved to 55.8 MPa. However, the CT20 film has the highest tensile strength, but the elongation at break is significantly reduced to only 7.43%. This reduction in ductility is a result of the increased tannic acid content, which promotes a higher cross-linking density and thus reduces the flexibility of the chains. Therefore, the CT10 film exhibits considerable mechanical strength and flexibility, making it suitable for flexible TENGs and sensors.
[0091] In order to study the triboelectric properties of CS and CT films, a TENG (triboelectric nanogenerator) was fabricated for electrical characterization. Figure 7 Shown is a size of 2 x 2 cm 2 The device structure consists of CS / CT film, triboelectric material and copper foil. Various triboelectric materials, including polyamide (PA), thermoplastic polyurethane (TPU), aluminum (Al), paper (Paper), polypropylene (PP), polyethylene terephthalate (PET), commercial polyimide (Kapton), polydimethylsiloxane (PDMS) and fluorinated ethylene propylene (FEP), are used as another triboelectric layer. Figure 8As shown, the collected transfer charge curves indicate that the CS pair presents consistent curves with all corresponding materials under contact and separation operations. Considering the strong negative polarity of FEP and the positive polarity of chitosan in the triboelectric series reported in previous studies, it can be inferred that CS has a more positive charge behavior than PA. The CT10 pair presents the opposite curve when in contact with PP and PET, indicating that the polarity of CT10 is between PP and PET. Compared with CT10, CT5 exhibits less negative charge behavior, which is between paper and PP. The test results of CT15 and CT20 are similar to those of CT10. It is obvious that with the addition of tannic acid, the CT film produces a significant polarity transition from positive to negative. Among them, the surface charge density of CT10 reaches 182μC m -2 This experiment demonstrated the effectiveness of polyphenol modification to induce triboelectric polarity transformation of chitosan.
[0092] The surface potentials of the different films were measured by Kelvin probe force microscopy (KPFM). Fig. 9 are the surface potentials of CS, PA, and CT5-20, which are 0.273 V, 0.203 V, -0.413 V, -0.507 V, -0.516 V, and -0.533 V, respectively. The lower surface potential observed in the CT film compared to CS indicates a higher work function, indicating a preference for negative triboelectric charge. Taking the surface potential energy of PA as V1 and the surface potential energy of CS and CT as V2, the estimated parameters a = 414.1, b = 191.8, and c = -9 are calculated. The fitting results are shown in Fig.10 And, by matching the expression with the consumed amino groups in Table 1, a prediction model can be obtained.
[0093] Table 1 Element characterization test results (%)
[0094]
[0095]
[0096] The above-described embodiments are only descriptions of preferred embodiments of the present invention, and are not intended to limit the scope of the present invention. It should be understood by those skilled in the art that the present invention can be applied not only to chitosan, but also to materials such as cellulose, lignin, sodium alginate and gelatin. Without departing from the spirit of the present invention, various modifications and improvements made by those skilled in the art to the technical solution of the present invention should fall within the scope of protection determined by the claims of the present invention.
Claims
1. A method for predicting the surface charge density of a triboelectric nanogenerator based on modified chitosan material, characterized in that: It includes the following steps: S1. Preparation of modified chitosan: Polyphenol is used as a modification material to chemically modify chitosan to obtain modified chitosan; S2. Triboelectric polarity test and quantitative characterization of modified chitosan: The modified chitosan is brought into contact with different materials in a known triboelectric series to generate an electric signal, and the relative positive and negative values of the electric signal and the saturated charge density are obtained, and the position of the modified chitosan in the known triboelectric series is determined according to the relative positive and negative values of the electric signal; S3. Obtain the surface potential energy and saturated charge density of the modified chitosan and the paired material: A friction nanogenerator is composed of modified chitosan and a pairing material, and the surface potential energy of the pairing material, the surface potential energy of the modified chitosan, and the saturated charge density of the friction nanogenerator are obtained respectively. S4. Construction of a surface charge density prediction model for triboelectric nanogenerators based on modified chitosan materials: The surface charge density prediction model of the triboelectric nanogenerator based on modified chitosan material is: σ c =a(V1-V2) 2 -b(V1-V2)-c <h2 style=";text-align:left;direction:ltr">C<h2 style=";text-align:left;direction:ltr"> p <h2 style=";text-align:left;direction:ltr"> =f(V2) Where: c is the surface charge density of the triboelectric nanogenerator; V1 is the surface potential energy of the paired material; V2 is the surface potential energy of the modified chitosan; a, b and c are the fitting parameters corresponding to different paired materials; C p is the polyphenol concentration; f is the functional relationship between the polyphenol concentration and the surface potential energy of the modified chitosan; According to the surface charge density prediction model of the triboelectric nanogenerator based on modified chitosan material, when the paired materials are determined, the surface charge density of the triboelectric nanogenerator can be directly determined according to the polyphenol concentration; This can guide the optimization of the triboelectric polarity of modified chitosan and improve the electrical output performance of the triboelectric nanogenerator.
2. The method for predicting the surface charge density of a triboelectric nanogenerator based on modified chitosan material according to claim 1, characterized in that: Step S1 specifically includes: S11, preparing a polyphenol solution: dissolving the polyphenol in a solvent to form a polyphenol concentration of C p The solution of C p The value range is (0%, 50%]; the solvent is a mixture of one or more of deionized water, ethanol, acetone and tetrachloromethane; S12, preparing a chitosan solution: dissolving chitosan in an acid solvent, and cleaning it to remove impurities and pollutants to obtain a chitosan solution; the acid solvent is a mixture of one or more of acetic acid, hydrochloric acid, nitric acid and phosphoric acid; S13, mixing the chitosan solution of S12 with the polyphenol solution of S11, and then placing in a mold to dry, to obtain modified chitosan.
3. The method for predicting the surface charge density of a triboelectric nanogenerator based on modified chitosan material according to claim 1, characterized in that: The materials in the known triboelectric sequence in step S2 include but are not limited to polyamide, thermoplastic polyurethane, polypropylene, polyethylene terephthalate, polydimethylsiloxane, polytetrafluoroethylene and polyperfluoroethylene propylene.
4. The method for predicting the surface charge density of a triboelectric nanogenerator based on modified chitosan material according to claim 1, characterized in that: Step S3 specifically includes the following sub-steps: S31, forming a friction nanogenerator by using modified chitosan and a matching material, wherein the friction nanogenerator is in a contact-separation mode; S32, using an electrometer to measure the charge signal of the contact and separation process, and obtaining the saturation charge density of the friction nanogenerator through the signal amplitude; S33. The surface potential energy of the modified chitosan material and the surface potential energy of the paired material during the contact separation process were measured using a scanning Kelvin probe microscope.
5. The method for predicting the surface charge density of a triboelectric nanogenerator based on modified chitosan material according to claim 1, characterized in that: Step S4 specifically includes the following sub-steps: S41. Based on the surface potential energy, a surface charge density prediction model of the friction nanogenerator in step S3 is constructed, and its expression σ c for: σ c =a(V1-V2) 2 -b(V1-V2)-c (1) Where: c is the surface charge density of the triboelectric nanogenerator; V1 is the surface potential energy of the paired material; V2 is the surface potential energy of the modified chitosan; a, b and c are the fitting parameters corresponding to different paired materials; S42, due to the surface charge density σ c It cannot be directly measured and obtained, and the saturation charge density σ must be measured first I , and then calculated by expression, the expression is: Where: z is the separation distance between the paired material and the modified chitosan; d1 and d2 are the thickness of the paired material and the modified chitosan, respectively; ε0 is the dielectric constant of air; ε1 and ε2 are the dielectric constants of the paired material and the modified chitosan, respectively; S43. The surface potential energy of modified chitosan is related to the modification degree, which corresponds to the polyphenol concentration. Therefore, the surface potential energy model of modified chitosan material is established according to the polyphenol concentration: <h2 style=";text-align:left;direction:ltr">V2 = f(C<h2 style=";text-align:left;direction:ltr"> p <h2 style=";text-align:left;direction:ltr"> ),(3) Where: C p is the polyphenol concentration; S44. According to formulas (1) and (3), a surface charge density prediction model of the friction nanogenerator based on modified chitosan is obtained. When different pairing materials are used to form a friction nanogenerator with the modified chitosan material, a surface charge density prediction model of the friction nanogenerator based on the modified chitosan material with different fitting parameters is obtained. The surface charge density prediction model of the friction nanogenerator based on modified chitosan using different pairing materials can directly obtain the surface charge density of the friction nanogenerator according to the polyphenol concentration, thereby guiding the optimization of the friction electric polarity of the modified chitosan and improving the electrical output performance of the friction nanogenerator.
6. The method for predicting the surface charge density of a triboelectric nanogenerator based on modified chitosan material according to claim 1, characterized in that: The chitosan in step S1 includes, but is not limited to, non-deacetylated chitin, chitosan with different deacetylation degrees, quaternary ammonium salt chitosan and carboxymethyl chitosan.
7. The method for predicting the surface charge density of a triboelectric nanogenerator based on modified chitosan material according to claim 1, characterized in that: The polyphenols in step S1 include, but are not limited to, tannic acid, catechins, dopamine and anthocyanins.
8. The method for predicting the surface charge density of a triboelectric nanogenerator based on modified chitosan material according to claim 1, characterized in that: The form of the modified chitosan in step S1 includes but is not limited to film, hydrogel, aerogel and block.
Citation Information
Patent Citations
Resistance tester based on friction nanometer generator and method thereof
CN109444545A
Method for measuring surface charge density of micro-nano particles
CN115656266A
Hyperelastic hydrophobic aerogel friction nano-generator with high triboelectric charge density and preparation method of super-elastic hydrophobic aerogel friction nano-generator
CN117895822A
Friction nano-generator with charge capture layer, preparation method, self-energized sensor and intelligent sensing system
CN118249670A
Friction nanometer generator and preparation method thereof
CN118441472A
Cited By
Method and system for testing electrical properties of coaxial double-electrode friction nanogenerator yarn
CN122545928A